A study of physical and mechanical properties using kenaf core as coarse aggregate replacement in concrete / Khairul Nazhan Khairul Izwan … [et al.] - Khairul Izwan, Khairul Nazhan; Ali Rahman, Azerai; Mohd Apandi, Nazirah; Shamsol, A’lia Sofea; Ahmad Zailani, Warid Wazien (Research Management Institute (RMI), 2023)
Kenaf is well known for its one of the highest rankings of biomass producers compared to other fibre crops which excessive amounts of biomass could lead to contamination of soil due to its pollutants elements. Not only that, the high demand for aggregate for concrete production requires massive use of natural stone materials which leads to the destruction of the ecological balance of the environment. As in Malaysia, kenaf core is commonly used and available in abundance after the processing of kenaf stems for bast fiber production. Thus, this research aims to determine the physical and mechanical properties of kenaf core as fine aggregate replacement in concrete. There were 45 samples of the concrete cube of 100 mm x 100 mm with the percentage used of 0, 5, 15 and 25 % kenaf core replacement. A density test was conducted as well as a compressive strength test to obtain the objectives of the study. Findings reveal that the control sample still has the highest value of compressive strength of 34.7 MPa while 5 % of kenaf core concrete shows 28.50 MPa which slight decrease in the value in comparison. The value then gradually decreases as the percentage of the kenaf core increases. The density test also reveals that 25 % kenaf core shows the lowest value of density by 1419.78 kg/m3 compared to normal concrete. Thus, this indicates that the optimum percentage of kenaf core used was 5 % even though it still did not surpass 0 % concrete.